USE OF THE BODY-ORIENTED THERAPY "BALLS" METHOD IN THE PSYCHOLOGICAL RECOVERY OF MILITARY PERSONNEL - Kulakevich, Maksym (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2024)
B a c k g r o u n d . In solving the psychological challenges of today, related to the consequences of hostilities, body-oriented methods are a number step in the direction of psychological recovery of Ukrainian military personnel. These psychotechniques not only help relieve emotional stress through physical activity, but also help restore harmony between body and soul. This deep and balanced approach supports mental resilience and adapts the military personnel to difficult situations. The article is aimed at presenting the author's method of body-oriented therapy "Balls" (V.G. Shevchenko) to the wider scientific community and its use in the psychological recovery of military personnel – participants in the russianUkrainian war. It is also important to substantiate the expediency of using this technique as one of the tools for comprehensive psychological recovery of combatants who have survived combat stress.M e t h o d s . The research used such theoretical methods as analysis, systematization and generalization of psychological data on the research problem. An analysis of scientific sources on psychological assistance to military personnel using body-oriented approaches was carried out, as well as a synthesis of this information for a better understanding of modern theoretical aspects of psychological recovery using the "Balls" technique.R e s u l t s . Primarily effective – the five-level training technique "Balls" as a complex of thirteen basic exercises with constantly increasing tasks was decoded within the framework of pilot projects of medical and psychological rehabilitation of the Ministry of Defense of Ukraine (2018) on the basis of the Military Medical Clinical Center of the Southern Region in the Odesa region and the base of winter sports "Tysovets" in the Lviv region, which covered about 700 of military personnel – participants in hostilities.C o n c l u s i o n s . A military personnel, after participating in training using the body-oriented "Balls" method, will experience positive changes in the perception and overcoming of stress, will gain new knowledge and skills in psychological self-regulation and will improve the quality of sleep, restore psychological balance, strengthen his internal resources and improve the general well-being It has been established that, in addition to the body-oriented effect, the "Balls" technique develops both simple and complex locomotion, promotes the development of psychomotor grace and contains both preventive and therapeutic effects in overcoming the effects of stress.